2023
DOI: 10.1021/acssensors.2c02104
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Room-Temperature NO2 Detection Using SnS2/MWCNT Composites and Accelerated Recovery Kinetics by UV Activation

Abstract: High performance with lower power consumption is one among the essential features of a sensing device. Minute traces of hazardous gases such as NO2 are difficult to detect. Tin disulfide (SnS2) nanosheets have emerged as a promising NO2 sensor. However, their poor room-temperature conductivity gives rise to inferior sensitivity and sluggish recovery rates, thereby hindering their applications. To mitigate this problem, we present a low-cost ultrasensitive NO2 gas sensor with tin disulfide/multiwalled carbon na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 67 publications
(204 reference statements)
0
14
0
Order By: Relevance
“…The specific surface area is an important parameter that affects the adsorption properties of sensing materials . To understand these properties, a BET analysis of nitrogen physisorption study was done on the MoS 2 and MoS 2 :2D-QC samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific surface area is an important parameter that affects the adsorption properties of sensing materials . To understand these properties, a BET analysis of nitrogen physisorption study was done on the MoS 2 and MoS 2 :2D-QC samples.…”
Section: Resultsmentioning
confidence: 99%
“…The specific surface area is an important parameter that affects the adsorption properties of sensing materials. 58 To understand these properties, a BET analysis of nitrogen physisorption study was done on the MoS NO 2 sensing measurement suggests that as-synthesized MoS 2 behaves as a p-type semiconductor (Figure 5a), and the resistance of the sensor deceased during the NO 2 (oxidizing gas) exposure. 4 Figure 4b Figure 5d shows the comparison in response to bare MoS 2 and MoS 2 :2D-QC sensors and found that the composite sensor response is 2.27 times larger than that of the bare sensor.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, the high concentration of SWCNTs significantly increases the composite’s effective conductivity, masking the gas-induced change in conductivity. This can clearly decrease the sensor response, which relies on changes in conductivity due to gas adsorption on MoS 2 . , The MoS 2 –SW20 sensor’s higher response could be attributed to its high specific surface area, high charge carrier density, the presence of defects, and synergistic effects that occur when a heterostructure is formed. ,, As a result, all subsequent DMF sensing measurements were performed using the MoS 2 –SW20 sensor. For the sake of comparison, response transients for the SWCNT-based device toward 5 ppm of DMF and NH 3 are also included in Figure S6.…”
Section: Resultsmentioning
confidence: 99%
“…The current–voltage ( I – V ) measurements were conducted using a Keithley SourceMeter (2612A). The sensing measurements were performed under ambient humidity conditions over a large span of time. , The sensor characterization was conducted with the lab-built static setup described in previous reports ,, and briefly discussed in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…After the sensing layer was applied, the sensor was dried in a vacuum oven at 80 °C for 10 h. A digital photograph of the two-terminal sensor device (1 cm × 1 cm) is shown in Figure S2. Sensing tests were performed using a homemade setup described in detail in other studies. , All gas-sensing tests were conducted at room temperature (20 ± 5 °C) and natural relative humidity levels over a long period of time. , The relative humidity (RH) of the experiment (40–80% RH) under a normal atmospheric environment was recorded during the sensing tests. In daily life, various stable RH conditions with a ±5% variation can be monitored .…”
Section: Methodsmentioning
confidence: 99%